Effective Communication of Family Hope Program (PKH) Facilitators to Beneficiary Families (KPM): A Study of P2K2 Activities in Kandang Mas Village, Bengkulu City - Liken, Enjli Lia; Octaviani, Vethy; Yanto, Yanto (Universitas Dehasen Bengkulu, 2025)
This research aims to examine the effective communication practices employed by facilitators of the Family Hope Program (PKH) in delivering Family Capacity Building Meetings (P2K2) to Beneficiary Families (KPM) in Kandang Mas Village, Bengkulu City. Using a descriptive qualitative method, the study applies the communication effectiveness model by Cutlip and Allen, which includes seven key indicators: Credibility, Context, Content, Clarity, Continuity and Consistency, Communication Channels, and Audience Capability.Findings reveal that communication is effective across all seven indicators. The facilitators' credibility is supported by formal recognition from the Ministry of Social Affairs and emotional bonds with the KPM. The communication context is enhanced through inclusive atmospheres, appropriate teaching media, and flexible scheduling. The content is delivered using official modules in simple language and practical examples. Clarity is achieved via structured messaging, while consistency is maintained through repeated but varied messages. Communication channels include a blend of digital tools like WhatsApp and face-to-face interactions. The facilitators also tailor their approach based on the educational and social background of the KPM, ensuring comprehension and active participation. Ultimately, P2K2 activities have succeeded in raising awareness, improving knowledge and skills, and encouraging behavioral change among KPM. This study underscores the critical role of tailored, multi-dimensional communication strategies in optimizing the impact of social programs like PKH.